Functional solubilization of the β2-adrenoceptor using diisobutylene maleic acid - Clare.R. Harwood (Elsevier, 2021)
Summary: The β2-adrenoceptor (β2AR) is a well-established target in asthma and a prototypical G protein-coupled receptor for biophysical studies. Solubilization of membrane proteins has classically involved the use of detergents. However, the detergent environment differs from the native membrane environment and often destabilizes membrane proteins. Use of amphiphilic copolymers is a promising strategy to solubilize membrane proteins within their native lipid environment in the complete absence of detergents. Here we show the isolation of the β2AR in the polymer diisobutylene maleic acid (DIBMA). We demonstrate that β2AR remains functional in the DIBMA lipid particle and shows improved thermal stability compared with the n-dodecyl-β-D-maltopyranoside detergent-solubilized β2AR. This unique method of extracting β2AR offers significant advantages over previous methods routinely employed such as the introduction of thermostabilizing mutations and the use of detergents, particularly for functional biophysical studies.